Electromagnetic freezing: a novel approach to the improvement of previously frozen beef - Looper, Jordan Taylor (My University, 2025)
The objective of this study was to determine the effect of electromagnetic field (EM) assisted freezing on the thawing yield, shelf-life, and tenderness of previously frozen beef striploins. Striploins were collected from both sides of 12 USDA Choice carcasses and halved into 2 equal parts (n=48), weighed, and temperature probes were inserted to measure internal temperature. Halves were randomly assigned to 0, 2, 4, or 8 kV of EM and frozen under the designated treatments in a walk-in freezer (-20°C) for 24 hours. Frozen cores were taken for X-ray computed tomography (XRCT) for ice crystal size analysis. Following the freezing treatment, striploin halves were thawed for 72 hours at 2°C, weighed, and fabricated into two 2.54 cm steaks and five 1.27 cm steaks from each portion. Steaks were then subjected to 10-day simulated display. Instrumental and descriptive color measurements were taken daily. Representative steaks from each portion were analyzed for muscle fiber spacing through histological analysis, Warner-Bratzler Shear Force (WBSF), purge and cook loss, fat content, moisture content, protein content, lipid oxidation, antioxidant capacity, protein degradation, pH, and free calcium analysis on days 0, 4, 7, and 10. Swabs and purge were also collected for aerobic plate count (APC) from both before and after freezing treatments. Samples from the higher treatments required a longer time to freeze than those from lower voltage and control (P<0.05), but total thawing yield was only higher in the samples from the 8 kV treatment (P<0.01). Degraded desmin and troponin-T percentages were lower in the higher voltage treatments compared to those from the lower voltage treatment and control (P<0.01). However, all samples with EM treatments reported a higher free calcium concentration compared to the those from the control (P<0.01). During the display period, 4kV samples showed least discoloration, while exhibiting highest a* and b* and hydrophilic antioxidant capacity than those from the other treatments (P<0.01). No differences were observed in APC, cook loss, WBSF, muscle fiber spacing, ice crystal size, lipid oxidation, or pH (P>0.05). EM assisted freezing demonstrated potential for improving thawing yield and shelf-life, and these findings provided a foundation to better determine the feasibility of large-scale integration of EM in the industry.
Keywords: Electromagnetic freezing; Striploin; Beef; XRCT; Quality